Gold nanoparticles attenuate the interferon-γ induced SOCS1 expression and activation of NF-κB p65/50 activity via modulation of microRNA-155-5p in triple-negative breast cancer cells - Farhana, Aisha; Alsrhani, Abdullah; Rasheed, Naila; Rasheed, Zafar (Frontiers in Immunology, 2023)
This is the first study that shows the therapeutic role of nanoparticles involved in the regulation of microRNA in cancer cells. This study evaluated that citrate-conjugated gold nanoparticles (AuNP) regulate miRNA in triple-negative breast cancer (TNBC), mediated through SOCS1-inducedNFkB signaling. The research sheds light on a potential mechanism of miRNA-mediated SOCS1 action, which may be harnessed for therapeutic intervention against the most aggressive form of breast cancer, TNBC. The study is an important foothold for further research. Subsequent studies to gain additional mechanistic insights can facilitate its translation to clinical settings.